Factors associated with family caregiver burden among frail older persons with multimorbidity - Ding, Gabriel Teck Yong (2022)
Introduction: Singapore is facing an ageing population and the care needs of the population will increase in tandem. A segment of this population would be living with multimorbidity and frailty. Frailty is defined as an age-related state characterised by reduced strength and physiologic malfunctioning. Multimorbidity refers to the coexistence of multiple chronic conditions in an individual. Older adults are more likely to have frailty and multimorbidity, and this would increase the burden of their caregiver. Our study aimed to determine the prevalence of caregiver burden for primary family caregivers of frail older adults with multimorbidity. We also investigated the factors that were associated with primary family caregiver burden. Methods: This was an interviewer-administered, cross-sectional study of primary family caregivers of frail older patients with multimorbidity that was conducted in two National Healthcare Group polyclinics. Convenience sampling was used. The 12-item Zarit Burden Index (ZBI) was used to assess primary family caregiver burden. The scores of the ZBI range from 0 to 48, with a score of 10 or above indicating that the primary family caregiver perceives burden. Descriptive statistics were used to provide information regarding the caregivers and the care recipients. Multivariable logistic regression was used to investigate the factors affecting primary family caregiver burden. Results: One hundred eighty-eight family caregivers were interviewed and 71.8% of them perceived burden on the ZBI. 59.6% were caregivers to their parents and 18.1% of them had multimorbidity. Almost two-thirds of the caregivers interviewed were female. After adjusting for other factors via multivariable analysis, the ethnicity of the caregiver and the increase in time spent caregiving per week were the two factors positively associated with family caregiver burden. A Chinese primary family caregiver had almost three times the odds of perceiving burden when compared to a non-Chinese primary family caregiver. Conclusion: Caregiver burden was high amongst primary family caregivers of frail older adults with multimorbidity. Being a Chinese primary family caregiver compared to non-Chinese ethnic groups as well as being a primary family caregiver who spent increased time caregiving per week were the two factors positively associated with family caregiver burden. Further exploratory, qualitative studies can be done to find out the reasons to Chinese primary family caregivers being more burdened compared to the non-Chinese primary family caregivers. In addition, the specific factors related to increased time caregiving per week and family caregiver burden can also be studied.